Relationship between Religious Coping, Pain Severity, and Childbirth Self-Efficacy in Iranian Primipara Women - Tahereh Sotudeh; Seyedeh Batool Hasanpoor-Azghady; Leila Amiri-Farahani (Obstetrics and Gynecology International)
Background. One of the important goals of midwifery support and care is to control labor pain and increase the ability to cope with pain. The use of religious coping may be effective in counteracting the stressors of labor, especially labor pain, as well as increasing the self-efficacy of labor. This study was conducted to determine the relationship between religious coping, pain severity, and childbirth self-efficacy in Iranian primipara women. Materials and Methods. This cross-sectional study was performed on 200 Iranian primiparous women referred to eight health centers in the capital of Hormozgan Province who were intending to have a normal vaginal delivery (NVD) in the Persian Gulf and Sharifi Hospitals. The sampling was multistage. Data were collected by demographic and fertility questionnaires, the Iranian Religious Coping Scale, the Childbirth Self-Efficacy Inventory, and the Visual Analog Scale for pain measurement. Results. Among the dimensions of religious coping, benevolent reappraisal had a significant direct relationship with pain severity, and negative religious coping had a significant inverse relationship with pain severity. In the case of childbirth self-efficacy subscales, the results showed dimensions of religious practices, benevolent reappraisal, and active religious coping had a significant direct relationship with outcome expectancy, and negative religious coping had a significant indirect relationship with outcome expectancy. Also, there was a significant direct relationship between religious practices and efficacy expectancy and a significant inverse relationship between negative and passive religious coping and efficacy expectancy. Conclusion. With increasing some dimensions of positive religious coping, the severity of labor pain and childbirth self-efficacy increases, and with increasing dimensions of negative and passive religious coping, childbirth self-efficacy decreases. These correlations were weak in all the mentioned results.